Serum macrophage‐derived chemokine/CCL22 levels are associated with glioma risk, CD4 T cell lymphopenia and survival time. Issue 4 (2nd February 2015) - Zhou, Mi; Bracci, Paige M.; McCoy, Lucie S.; Hsuang, George; Wiemels, Joseph L.; Rice, Terri; Zheng, Shichun; Kelsey, Karl T.; Wrensch, Margaret R.; Wiencke, John K.
<x xml:space="preserve">Abstract</x> Defects in antigen presenting cell function have been implicated in glioma immunosuppression. We measured peripheral CCL22, a dendritic cell/macrophage derived T cell trafficking chemokine, in sera from 1, 208 glioma cases and 976 controls to assess whether it might provide a biomarker of glioma risk, survival and immune dysfunction. Cluster models were used to examine the relationship between CCL22 and glioma risk. Patient survival was assessed using Cox regression models. We also examined the relationship between CCL22 levels and CD4 cell counts, as well as allergy history and IgE levels. CCL22 levels were significantly lower among glioma cases compared with controls (Mean ± SEM: 1.23 ± 0.03 ng/mL in cases vs. 1.60 ± 0.03 ng/mL in controls, p < 0.0001) and this difference remained significant even after controlling for other covariates in the cluster models (highest quartile versus lowest Odds Ratio = 0.21, p < 0.0001). CD4 cell counts were positively correlated with CCL22 in glioma cases (Spearman r2 = 0.51, p < 0.01) and were significantly lower in cases compared with controls. Higher CCL22 levels were associated with longer survival in all cases combined and in GBM cases (hazard ratioallcases = 0.81; 95% CI: 0.72–0.91, p = 0.0003). CCL22 levels were not associated with IgE level or self‐reported allergies. Circulating CCL22 levels are related to both glioma risk and survival duration independent of age, histology, grade and IDH mutation status. CCL22 should be considered a marker of immune status with potential prognostic value.